Quantification of Baboon Thymopoiesis in Porcine Thymokiciney Xenografts by the Signal-Joining T-Cell Receptor Excision Circle Assay - Tena, Aseda (2011)
BACKGROUND: Transplantation of vascularized donor thymic tissue along with a kidney transplant has markedly improved graft survival across the discordant pig-to-baboon xenogeneic barrier. To quantify the production of baboon T cells by the porcine thymic tissue, we recently developed an assay to measure the excised DNA products of baboon T-cell receptor (TCR) gene rearrangement (signal-joining TCR excision circles, sjTREC). METHODS: Initial polymerase chain reaction (PCR) analysis documented that TCR δREC-ψJα rearrangement occurs in baboons. Primers, specific to baboon sjTREC sequence were designed and used to quantify sjTREC molecules in peripheral blood mononuclear cells and thymic tissue using a quantitative PCR assay. RESULTS: sjTREC levels were higher in phenotypically naïve (CD3(+)CD45RA(++)) T cells (650 copies/100,000 cells) than in phenotypically memory (CD3(+)CD45RA(low)) T cells, with sjTREC below the limit of detection (40 copies/100,000 cells). Surgical removal of the native thymus in two baboons led to a significant decrease of sjTREC in peripheral blood (from 1104 and 920 copies to 184 and 190 copies/100,000 cells, respectively), confirming the role of the thymus in maintaining the peripheral T-cell pool. In two thymectomized baboons that received porcine thymokidney xenografts, sjTREC levels remained low in the peripheral blood (<40 copies/100,000 cells), but increased to 52 and 192 copies/100,000 cells in thymic biopsies, implying that baboon thymopoiesis had begun to occur in the porcine thymic xenografts. CONCLUSIONS: Baboon sjTREC can be quantified by quantitative PCR using primers specific to baboon sequence. Initial results suggest that baboon thymopoiesis occurs in vascularized porcine thymus xenografts.